Open Textbook Author Journeys: Internal Conversations and Cycles of Time - Cox, Glenda; Willmers, Michelle; Masuku, Bianca (International Review of Research in Open and Distributed Learning, 2022)
One of the challenges experienced in South African higher education (HE) is a lack of access to affordable, appropriate textbooks and other teaching materials that can be legally shared on online forums and the Internet. There are also increasing calls to address transformation and social justice globally and in South African HE through curriculum transformation. This article draws on the research of the Digital Open Textbooks for Development initiative at the University of Cape Town (UCT). It presents the journeys of four open textbook authors at UCT in relation to the social injustices they witness in their classrooms. It also makes use of Margaret Archer’s social realist approach to explore dynamics related to open textbook authors’ agency and ultimate concerns, as well as how their internal conversations shape their practices and approaches to open textbooks. Open textbooks are framed as a set of practices that play out in varying cycles of time and hold promise in terms of addressing the need for greater access and inclusivity in HE.